Detecção de genes de resistência de Acinetobacter baumanii e Pseudomas aeruginosa multirresistentes e caracterização clínica dos pacientes em hospital público de Sergipe - Santos, Fernanda Lays Souza Góes (2015)
Infections caused by Acinetobacter baumannii and Pseudomonas aeruginosa multiresistant are responsible for high morbidity and mortality, failure of drug therapy, increased hospital stay and consequently the financial impact on the health system. However, while the occurrence of these bacteria to configure a public health problem, numerous studies reveal that it is scarce information about the resistance genes present in multi-drug resistant bacteria. This reality associated with the negative impact of these on society, justifies the importance of detecting the resistance genes of A. baumannii and P. aeruginosa multiresistant and clinically characterize patients from a public hospital in Sergipe. It is an analytical prospective cohort study and a quantitative approach. The collection of clinical data of patients was carried out through a specifically designed form. Strains of A. baumannii were subjected to PCR for identification of resistance genes (blaIMP, blaVIM, blaSIM, bla OXA-51, blaOXA-58, blaOXA-23 and blaOXA-24) and P. aeruginosa the blaSPM genes, blaVIM, blaIMP, blaKPC. Descriptive analyzes were performed, the Chi-square and Fisher exact tests, with 5% significance level. The software used was R version 3.1.2. The sample consisted of 119 patients. Of the 43 patients with P. aeruginosa isolates, 33 were male (76.7%) with mean age of 46.2 years. Twenty-eight were admitted to the ICU (65.1%) and 13 (30.2%) diagnosed with head trauma (TBI). Of the 76 patients with isolates of A. baumannii, 59 (77.6%) were male, mean age of 44.4 years. Fifty patients (65.8%) were from the ICU and 18 (23.7%) diagnosed with TBI. The median number of days of hospitalization was statistically significant between bacteria. Among the isolation sites, there is urine to P. aeruginosa, with 16 samples (37.2%) and tracheal aspirate for A. baumannii with 32 (42.1%) strains. A urinary catheter was the most used device in patients with isolates of A. baumannii (93.4% - 71) and the central venous catheter in patients with P. aeruginosa (93% - 40). All patients with P. aeruginosa isolates made use of carbapenems and 98.6% (75) of A. baumannii. It found statistically significant differences between bacteria in the use of aminoglycosides, 3rd generation cephalosporins and tigecycline. In P. aeruginosa was no significant difference in the use of oxacillin and cephalosporins of 1st and 3rd generations and polymyxin in the various sectors of the hospital. All the samples of A. baumannii and P. aeruginosa were susceptible to colistin, ranging between MIC <= 0.5 and 2. The majority (55.8% - 24) patients with P. aeruginosa and A. baumannii (52.6% - 40) died. Among the 76 strains of A. baumannii, 56 (73.6%) had concomitant both blaOXA-51 and blaOXA-23 genes. Among the 43 strains of P. aeruginosa, 28 (65.1%) had the blaSPM gene. It was concluded that the A.baumannii was more frequent than P. aeruginosa. There was a significant predominance of Pseudomonas and Acinetobacter in the urine in tracheal aspirates. Carbapenems was widely used throughout the hospital stay of patients with Acinetobacter and Pseudomonas isolates in different hospital departments. Most Pseudomonas strains showed blaSPM resistance gene and Acinetobacter blaOXA-23 genes and blaOXA-51 concurrently. The mortality of patients with Acinetobacter and Pseudomonas was greater than 50%.